Activity–composition relations for the calculation of partial melting equilibria in metabasic rocks. (31st August 2016) - Green, E. C. R.; White, R. W.; Diener, J. F. A.; Powell, R.; Holland, T. J. B.; Palin, R. M.
Abstract: A set of thermodynamic models is presented that, for the first time, allows partial melting equilibria to be calculated for metabasic rocks. The models consist of new activity–composition relations combined with end‐member thermodynamic properties from the Holland & Powell dataset, version 6. They allow for forward modelling in the system Na 2 O–CaO–K 2 O–FeO–MgO–Al 2 O 3 –SiO 2 –H 2 O–TiO 2 –Fe 2 O 3 . In particular, new activity–composition relations are presented for silicate melt of broadly trondhjemitic–tonalitic composition, and for augitic clinopyroxene with Si–Al mixing on the tetrahedral sites, while existing activity–composition relations for hornblende are extended to include K 2 O and TiO 2 . Calibration of the activity–composition relations was carried out with the aim of reproducing major experimental phase‐in/phase‐out boundaries that define the amphibolite–granulite transition, across a range of bulk compositions, at ≤13 kbar.